2012
DOI: 10.1007/s00122-012-1974-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RFLP and NBS/PK profiling markers for disease resistance loci in genetic maps of oats

Abstract: Two of the domains most widely shared among R genes are the nucleotide binding site (NBS) and protein kinase (PK) domains. The present study describes and maps a number of new oat resistance gene analogues (RGAs) with two purposes in mind: (1) to identify genetic regions that contain R genes and (2) to determine whether RGAs can be used as molecular markers for qualitative loci and for QTLs affording resistance to Puccinia coronata. Such genes have been mapped in the diploid A. strigosa × A. wiestii (Asw map) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
15
0
2
Order By: Relevance
“…Unlike the pathosystem of E. grandis and P. psidii, the high number of resistant genes in maize and Arabidopsis may make it easier to identify large amount of RGAs. The effectiveness of this technique for mapping resistance genes were developed in several crops, including melons, chickpeas, soybeans, and oats have been well documented (Garcia-Mas et al 2001;Huettel et al 2002;Wang et al 2004;Satheeskumar et al 2011;Sanz et al 2013 Studies involving a larger number of RGAs can increase the chances of identifying loci linked to the Ppr1 gene, as well as allow for inferences about the presence or absence of an NBS domain in this gene. However, as NBS domains are found in many protein families, including atpases, elongation factors, and G proteins (Saraste et al 1990), it may be difficult to identify RGAs contributing to disease resistance as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the pathosystem of E. grandis and P. psidii, the high number of resistant genes in maize and Arabidopsis may make it easier to identify large amount of RGAs. The effectiveness of this technique for mapping resistance genes were developed in several crops, including melons, chickpeas, soybeans, and oats have been well documented (Garcia-Mas et al 2001;Huettel et al 2002;Wang et al 2004;Satheeskumar et al 2011;Sanz et al 2013 Studies involving a larger number of RGAs can increase the chances of identifying loci linked to the Ppr1 gene, as well as allow for inferences about the presence or absence of an NBS domain in this gene. However, as NBS domains are found in many protein families, including atpases, elongation factors, and G proteins (Saraste et al 1990), it may be difficult to identify RGAs contributing to disease resistance as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…There are currently more than 100 described Pc genes (Sanz et al 2013 ;Gnanesh et al 2014 ), but because their chromosomal locations have not been determined, many could be the same or allelic. Most Pc genes are inherited dominantly, but some are either partially dominant or recessive (Simons et al 1978 ).…”
Section: Crown Rust ( Pca ) and Stem Rust ( Pga ) Resistance Genesmentioning
confidence: 99%
“…Cloning and study of members of defi ned resistant gene families, such as wheat Lrk10 -type genes in oats (Cheng et al 2003 ). Sanz et al ( 2013 ) found that nucleotide binding site (NBS) and protein kinase (PK) based markers cover partly complementary regions of oat genomes. Markers of the different classes obtained were found to be associated with the two resistance loci, PcA and R-284B-2, mapped on A. strigosa × A. wiestii (Asw map), and with fi ve out of eight QTLs for partial resistance in the MN841801-1 × Noble-2 (MN) map.…”
Section: Rustmentioning
confidence: 99%
“…However, efforts have been made to characterize oat RGAs that might be useful in the development of genetic markers of resistance. Using individual RGA amplicons and motif-directed-profiling, a number of markers have been located in several oat genetic reference maps [14, 21]. Some of these markers lie close to previously mapped Mendelian genes for resistance.…”
Section: Introductionmentioning
confidence: 99%